(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify: - The impact of analog thinking strategy on developing habits of mind among middle school students with the subject of art education and measuring the size of the effect. The researcher adopted the experimental curriculum with an experimental design for the two equal groups for pre and post testing, and the research community was determined by students of the second intermediate grade in middle and high schools in the General Directorate of Baghdad Education Rusafa / Third for the academic year (2020-2021), as the intermediate (Osama bin Zaid) for boys was chosen intentionally From a total of (53) intermediate and secondary students, Hall (2) was chosen randomly to be the experimental group of (15) students, which would study the subject according to the analog thinking strategy, and Hall (7) to be the control group with (15) students that would study the subject according to the usual method of Between (15) halls in the school, according to the instructions approved by the Ministry of Education and Parliamentary Health and the social distancing due to the (Corona) virus, and thus the total sample is (30) students, and the two research groups were equal in (chronological age, IQ test, academic achievement of parents, Mothers’ academic achievement, previous information test, previous achievement of the first course in the first intermediate grade, habits of mind test), the researcher’s use of the statistical bag (Spss) and using the (Man and Tenny) test for two independent samples The results showed that there were no statistically significant differences between the mean scores of the two groups, which indicates the parity of the two groups in the previous variables. The scientific material was defined by topics (planning, colors, perspective, ornament) and related literature from the teacher’s guide for art education for intermediate stage F2 (2018), and the time period of (nine weeks) at the rate of one session per week, and with regard to the research tool, the researcher built a scale for the habits of the mind In the art education subject, which the researcher adopted in building it on the classification (Costa and Calic, 2003), the scale consisted of (40) paragraphs, including positive and negative paragraphs distributed among six mental habits, and the apparent validity of the tool was verified by presenting it to a group of arbitrators and specialists through appearance The general scale of the scale, the type of vocabulary, how it was formulated, the clarity and relevance of the paragraphs, and the validity of the construction was verified by finding the distinctive strength of the scale paragraphs, and the validity of the construction was also achieved by finding the method of correlating the degree of each paragraph with the total degree of the scale, and finding the style of the paragraph degree and the degree of the field and the degree The field is the total degree. The experiment started on Sunday (11/30/2020) for the two research groups (experimental and control) and ended on Monday (01/25/2021). The two groups and the results showed that the researcher reached the superiority of the experimental group that was studied according to the analog thinking strategy over the control group that was studied in the usual way.